POLICY ANALYSIS FOR PREPARING SERVICE TARIFFS FOR BLUD RSU CUT MEUTIA ACEH UTARA - Laksamana, Harry; Fithra, Herman; Nurhafni, Nurhafni; Fazil, Muhammad (Jurnal Sosiologi Dialektika Sosial, 2025)
This study analyzes the policy of preparing health service tariffs at the Cut Meutia General Hospital (RSU) of North Aceh Regency, which has the status of a Regional Public Service Agency (BLUD). Cut Meutia Hospital is the only advanced health facility in North Aceh and has a vital role in providing quality health services. This study focuses on how service tariffs are structured by considering the cost per unit of service, people's purchasing power, and the operational sustainability of sick homes. The results of the study show that Cut Meutia Hospital uses a tariff policy that includes cost recovery, cost plus, and cost minus. Although the rates set tend to be high for the lower middle economic community, this policy aims to ensure the sustainability of hospital operations and the quality of services provided. The process of preparing tariffs follows the regulations of the Regent of North Aceh, involving hospital management and other related parties. Periodic evaluations of tariffs need to be carried out in order to adjust to the needs of the community and service costs. This study provides an understanding of the importance of tariff policies in improving access and quality of health services and provides recommendations for hospital managers and local governments in setting fair and efficient rates.